If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -21 = 2m + 7 Reorder the terms: -21 + 9m = 2m + 7 Reorder the terms: -21 + 9m = 7 + 2m Solving -21 + 9m = 7 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -21 + 9m + -2m = 7 + 2m + -2m Combine like terms: 9m + -2m = 7m -21 + 7m = 7 + 2m + -2m Combine like terms: 2m + -2m = 0 -21 + 7m = 7 + 0 -21 + 7m = 7 Add '21' to each side of the equation. -21 + 21 + 7m = 7 + 21 Combine like terms: -21 + 21 = 0 0 + 7m = 7 + 21 7m = 7 + 21 Combine like terms: 7 + 21 = 28 7m = 28 Divide each side by '7'. m = 4 Simplifying m = 4
| 3(t-11)=9+t | | -9x-92=5x-60 | | 8(9x-2)=72x-2 | | 18+10=-4(2x-7) | | 5x-21=x+31 | | 39=8x-(2x-3) | | 18-4e=e+3 | | 5r-(2r+18)=16 | | -2(2+3x)=-28+6x | | -2a+7-3(-9-4a)= | | -17-2x=9+t | | 7x=--6 | | -.6a=2 | | r+12= | | dfghj=k | | 7n+6n+-5=4n+4 | | 4+2m=6+2m | | 4d+2(7+-2)= | | -1.6=x+1.1 | | 5x-2-x=30 | | c-33+2=443 | | 5-3=43 | | 6z-19-z+4=0 | | 4x+2x+3=9 | | (-4x^2+3x-1)-(4x+2)= | | 4.3=b-1 | | -8+5x-7x=-16 | | 5.16-p=15.48 | | 12-2c+6c= | | 12-22x= | | 0.75(-6)-6= | | 4r-r= |